PERAN GANDA DAN FLEKSIBILITAS JAM KERJA TERHADAP PRODUKTIVITAS KERJA BURUH PEREMPUAN PADA UKM KONVEKSI BATIK SEMARANG 16 - Anis Indrawati; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2019)
The role of women in society nowadays is not just being a housewife, they participate to work because of the economic factors in their life. One of the sectors which likely to be chosen by people is the informal sector such as UKM. Many informal business have flexible working hours and give the workers a choice to choose their working time which suitable the capability of work. Dual role and flexible working hours can be a specific factors in case to increase productivity at work.  This research was conducted at UKM Konveksi Batik Semarang 16, aiming to describe and analysis of dual role and flexible working hours towards the productivity of women laborers. The method used in this research is a qualitative research. The type used in this research is a descriptive qualitative method. This research is using accumulation with in depth interview with the research subject. This research shows that the dual role has not been always running well and balance. The productivity could be decrease because of the dual role has not been balance. The productivity shows good result of their quantity and quality production, but their fine timing often lack because of their performances. Flexible working hours can give a positive impact in their free time with their family but working hours like that could give an affect to their health due to exhaustion factor. Suggestions that can be given are 1) Women laborers must balance their dual role much better than before and try to divide up the house tasks with their husband 2) The owner can offer flexible working hours schedule to their workers 3) Women laborers should balance their dual role life especially when conflict happens and they must pay attention to their health.